PROTOTYPE MONITORING DAN PENGONTROLAN SUARA, SUHU DAN KELEMBABAN RUMAH BURUNG WALET BERBASIS INTERNET OF THINGS - Sahrul; Adi Chandra; Muhammad Awal Nur (Journal System Information And Computer, 2023)
This study aims to: (1) make a prototype of a tool that can monitor and control the sound, temperature and humidity of the swiftlet house based on the Internet of Things. (2) find out the implementation of a prototype monitoring and control of sound, temperature and humidity based on the Internet of Things in the swallow's house. This study uses a prototype research method (prototyping). The stages of making tools using prototypes are gathering requirements, building prototypes, evaluating prototypes, coding the system, testing the system, evaluating the system, using the system. This study uses data collection techniques, namely, observation, interviews, literature study, questionnaires, documentation. The research results show that: (1) prototype monitoring and controlling sound, temperature and humidity of internet-based swallow bird houses was designed with flowcharts and system block diagrams and was made using sensors DHT11, RTC DS3231, DfPlayer mini, speakers, water pumps and NodeMCU ESP8266 and use the blynk application. The blynk application can run on smartphone specifications with a minimum RAM of 1.5 GB with Android version 6.0 and above. (2) implementation of a prototype monitoring and controlling sound, temperature and humidity based on the internet of things swallow bird house can perform watering automatically properly, the system can also display humidity and temperature conditions using the blynk application on a smartphone. This prototype can also play sound properly according to the time specified and displayed in the blynk application. Where the watering system occurs when the temperature reaches 29o C it will do automatic watering so that it reduces temperature conditions, if the temperature is below 29o C then the watering will stop automatically. Meanwhile, the speaker will sound automatically at 05.00 WITA and if it is at 20.00 WITA, the speaker will turn off automatically.